Preliminary description of two new species of Cephalopods (Cephalopoda: Brachioteuthidae) from South Atlantic and Antarctic waters - Lipinski, Marek R. (Morski Instytut Rybacki (Gdynia), 2001)
Two species of cephalopods belonging to the squid family Brachioteuthidae are described for the first time. Brachioteuthis linkovskyi sp. nov. is a large brachioteuthid (120 mm mantle length [ML], mature male) collected at night in 720 m water depth using a krill trawl about 600 miles south-east of Montevideo (South Atlantic). Characters differentiating it from other brachioteuthids include: a fibrous net covering the head and arms ( at least in mature males), sucker dentition on arms and tentacular clubs, and tentacular club and stalk morphology. Slosarczykovia circumantarctica gen. et sp. nov. is a large brachioteuthid (150 mm ML, but 170 mm has been reported in the literature), which has often puzzled teuthologists and has been reported previously from the Antarctic waters. Characters of the new genus include subequal suckers on the tentacular clubs and a delicate net of fibrous tissue covering the entire bodies of both sexes for individuals of about 60 mm and longer. The holotype for the new genus and species was collected by a krill trawl in the waters adjacent to the Wilkes Land (Antarctica) in January 1978. Slosarczykovia circumantarctica is one of the most common squids in the Antarctic waters and occurs around the Antarctic.